Enhancing strength and ductility of AZ31 magnesium alloy sheets by the trapezoid extrusion. (February 2014) - Yang, Q. S.; Jiang, B.; Zhou, G. Y.; He, J. J.; Pan, F. S.
<x content-type="archive" xml:space="preserve">Abstract</x> The microstructure evolutions and mechanical properties of AZ31 magnesium alloy sheets processed by the conventional extrusion and the trapezoid extrusion (TE) were investigated. The textural evolutions of TE sheets at near surface are different throughout the sheet thickness direction due to an additional shear deformation. This enforces the basal plane to tilt toward the direction of shear deformation. Moreover, it weakens the basal texture intensity. Trapezoid extrusion process exhibits a considerable grain refinement. Improved strength and ductility of magnesium alloys sheets were achieved by TE approach due to the tilted weak basal texture and the grain refinement.